#Science: The Potential and the Challenges of Utilizing Social Media and Other Electronic Communication Platforms in Health Care. Issue 1 (13th September 2019) - Gijsen, Violette; Maddux, Michele; Lavertu, Adam; Gonzalez‐Hernandez, Graciela; Ram, Nilam; Reeves, Byron; Robinson, Thomas; Ziesenitz, Victoria; Shakhnovich, Valentina; Altman, Russ
Abstract : Electronic communication is becoming increasingly popular worldwide, as evidenced by its widespread and rapidly growing use. In medicine, however, it remains a novel approach to reach out to patients. Yet, they have the potential for further improving current health care. Electronic platforms could support therapy adherence and communication between physicians and patients. The power of social media as well as other electronic devices can improve adherence as evidenced by the development of the app bant . Additionally, systemic analysis of social media content by Screenome can identify health events not always captured by regular health care. By better identifying these healthcare events we can improve our current healthcare system as we will be able to better tailor to the patients' needs. All these techniques are a valuable component of modern health care and will help us into the future of increasingly digital health care.